2004
DOI: 10.1080/15287390490447287
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament 200 as an Indicator of Differences Between Mipafox and Paraoxon Sensitivity in SY5Y Neuroblastoma Cells

Abstract: Organophosphorus (OP) compounds produce potent neurotoxic effects in humans, including organophosphorus-induced delayed neuropathy (OPIDN). This investigation examined the potential for the 200-kD neurofilament protein (NF200) and other neuronal proteins to serve as indicators for neurite damage in a differentiated SY5Y human neuroblastoma cell culture system. Mipafox, which induces OPIDN, increased NF200 protein expression in SY5Y cells differentiated with human recombinant beta-nerve growth factor (NGF, 20 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 36 publications
2
9
1
1
Order By: Relevance
“…NEF protein levels are correlative to neurite outgrowth, and its gene expression is dramatically altered in neurodegenerative diseases, including Parkinson's disease and Alzheimer's disease [60]. NEF protein levels have also been suggested as a potential biomarker in organophosphorous neurotoxicity [36]. Furthermore, neurite outgrowth can be promoted by nerve growth factor (NGF) via the regulation of NEF gene expression and NEF protein phosphorylation [61].…”
Section: Resultsmentioning
confidence: 99%
“…NEF protein levels are correlative to neurite outgrowth, and its gene expression is dramatically altered in neurodegenerative diseases, including Parkinson's disease and Alzheimer's disease [60]. NEF protein levels have also been suggested as a potential biomarker in organophosphorous neurotoxicity [36]. Furthermore, neurite outgrowth can be promoted by nerve growth factor (NGF) via the regulation of NEF gene expression and NEF protein phosphorylation [61].…”
Section: Resultsmentioning
confidence: 99%
“…Mipafox and paraoxon are two well-studied OPs; the first has been described as inducer of OPIDN, and the second is known as an acutely toxic, but non-neuropathic OP (Ehrich et al, 1997). Studies in human and murine neuroblastoma cell lines have shown that paraoxon (non-neuropathic) inhibits AChE even at nanomolar concentrations, but only inhibits NTE at high concentrations; while mipafox (neuropathic) inhibits AChE weakly, but inhibits NTE at low concentrations (Ehrich et al, 1997;Cho and Tiffany-Castiglioni, 2004). The inhibition of AChE is enough for the generation of the cholinergic syndrome, but not for the development of OPIDN, which depends on the inhibition and aging of at least 70% of NTE (Ehrich et al, 1997).…”
Section: Introductionmentioning
confidence: 98%
“…The use of different in vitro cell culture assays for predicting the in vivo effects of these chemicals have been extensively reviewed in recent years and the issues pertaining to their use have also been discussed [1-5]. The in vitro systems have been developed and utilized not only to understand the mechanisms of toxicity at the molecular and cellular levels but also to screen potential neurotoxicants.…”
Section: Introductionmentioning
confidence: 99%